2019
DOI: 10.1080/19490976.2019.1638724
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of enteric bacterial infections and modulation of gut microbiota with conjugated linoleic acids producing Lactobacillus in mice

Abstract: Probiotics are recognized for outcompeting pathogenic bacteria by competitive receptormediated colonization and secretion of functional metabolites which are antimicrobial against certain microbes as well as improving host's gut health and immunity. Recently, we have constructed a bioactive Lactobacillus casei (LC) strain, LC +mcra , by inserting mcra (myosin crossreactive antigen) gene, which stimulates the conversion of conjugated linoleic acids. In this study, we evaluated the modulation of gut microbiome a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 70 publications
4
35
0
1
Order By: Relevance
“…And we believe that CLA reduces the Salmonella intestinal colonization including several aspects. Firstly, CLA treatments could signi cantly upregulated the concentration of tight junction proteins (ZO-1, occludin, E-cadherin 1 and claudin-3) and ameliorated epithelial apoptosis [96][97][98], which protect intestinal from the impairments caused by Salmonella infection. Secondly, CLA can modulate the gut in ammation including attenuated the expression of proin ammatory cytokines (TNF-α, INF-γ, IL-1β, and IL-6 and IL-17) while upregulating the level of the anti-in ammatory cytokine IL-10 [96][97][98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
“…And we believe that CLA reduces the Salmonella intestinal colonization including several aspects. Firstly, CLA treatments could signi cantly upregulated the concentration of tight junction proteins (ZO-1, occludin, E-cadherin 1 and claudin-3) and ameliorated epithelial apoptosis [96][97][98], which protect intestinal from the impairments caused by Salmonella infection. Secondly, CLA can modulate the gut in ammation including attenuated the expression of proin ammatory cytokines (TNF-α, INF-γ, IL-1β, and IL-6 and IL-17) while upregulating the level of the anti-in ammatory cytokine IL-10 [96][97][98][99][100][101].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that CLA reduces intestinal colonization by Salmonella by in uencing several processes. Firstly, CLA treatment considerably upregulated the concentration of tight junction proteins (ZO-1, occludin, E-cadherin 1 and claudin-3) and ameliorated epithelial apoptosis [96][97][98], which protects intestinal cells from the impairment caused by Salmonella infection. Secondly, CLA modulates gut in ammation by attenuating the expression of proin ammatory cytokines (TNF-α, INF-γ, IL-1β, and IL-Lactobacillus competitively excludes Salmonella in a mixed-culture condition [102].…”
Section: Discussionmentioning
confidence: 99%
“…and and upregulating the level of anti-in ammatory cytokine IL-10[96][97][98][99][100][101]. Thus, CLA exhibits anti-in ammatory effects that reduce gut colonization by Salmonella.…”
mentioning
confidence: 99%
“…The amount and types of bioactive metabolites produced by beneficial microbes are vastly influenced by undigested dietary components and/or prebiotics 11,13 . Any potential prebiotic intended for use has to comply with some regulations, like possessing the "Generally Recognized as Safe (GRAS)" status, being assessed for appropriate dose and potential side effects, must be free of contaminants and impurities and must not cause alterations to the intestinal microbiota that could negatively affect the host 18 .…”
mentioning
confidence: 99%
“…Considering this, our research team over-expressed the myosin-cross-reactive antigen (Mcra) ('mcra' gene obtained from L. rhamnosus, another probiotic strain) 33 for linoleate isomerase over-production in Lactobacillus casei (LC). The mcra over-expressing probiotic, named as "LC +mcra ", showed enhanced activities, including anti-inflammatory and antimicrobial effects both in vitro and in vivo animal model (mice) 13,31 . It has also been reported that LC +mcra induced no detrimental effect on mice gut, rather it improved the murine gut health through the modulation gut microbiome 13 .…”
mentioning
confidence: 99%